Runoff change scenarios based on regional climate change projections in mountainous basins in Slovakia - ŠTEFUNKOVÁ, Zuzana; HLAVČOVÁ, Kamila; LAPIN, Milan (Contributions to Geophysics and Geodesy, 2013)
In the study the potential impact of climate change on river runoff in the upperHron River, V´ah River, and Laborec River basin was evaluated using the Hron conceptualspatially-lumped rainfall-runoff model, which was driven by regional circulation modelsof atmosphere. The rainfall-runoff model was calibrated with data from the 1981–1995period and validated with data from the 1996–2010 period. Changes in climate variables inthe future were expressed by three different regional climate change projections: KNMI,MPI and ALADIN-Climate for the period 1961–2100. Changes in the seasonal runoffdistribution were evaluated by a comparison of the simulated long-term mean monthlydischarges in the river basin outlets in future decades with the present stage.